2020
DOI: 10.1186/s40364-020-00218-z
|View full text |Cite
|
Sign up to set email alerts
|

Redox signaling and Alzheimer’s disease: from pathomechanism insights to biomarker discovery and therapy strategy

Abstract: Aging and average life expectancy have been increasing at a rapid rate, while there is an exponential risk to suffer from brain-related frailties and neurodegenerative diseases as the population ages. Alzheimer’s disease (AD) is the most common neurodegenerative disease worldwide with a projected expectation to blossom into the major challenge in elders and the cases are forecasted to increase about 3-fold in the next 40 years. Considering the etiological factors of AD are too complex to be completely understo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 139 publications
(152 reference statements)
3
32
2
Order By: Relevance
“…These deposits coalesce to form the miliary structures that are known as plaques [7] . Interestingly, recent data suggest the importance of cholesterol for the γ-secretase cleavage of amyloid precursor protein, the last step of Aβ formation [32] .…”
Section: Physiopathological Manifestationsmentioning
confidence: 99%
See 4 more Smart Citations
“…These deposits coalesce to form the miliary structures that are known as plaques [7] . Interestingly, recent data suggest the importance of cholesterol for the γ-secretase cleavage of amyloid precursor protein, the last step of Aβ formation [32] .…”
Section: Physiopathological Manifestationsmentioning
confidence: 99%
“…Indeed, recent observations indicated that Pre-translational mRNA oxidation synthetize peptides that are prone to aggregate [199] . mRNA oxidation seems to be a cytoanatomically selective event that hit mRNAs translated by ribosomes that reside tethered to the mitochondrial outer membrane [32] . The aggregates heavily impair the physiological cell functions.…”
Section: Oxidative Stressmentioning
confidence: 99%
See 3 more Smart Citations